A Novel Approach to Quantitative Structure-Property Relationships in Antioxidants - Rosas-Romero, Alfredo J.; Rojano, Benjamín; Hernández, Carmen A.; Martínez Machado, Carlos; Silva, Judith; Herrera, Julio C. (Ciencia, 1970)
Â  The autoxidation of linoleic acid, in presence of varying concentrations of antioxidants, was followed by measuring the decoloration of -carotene. The absorbance versus time curves were fitted to the following expression: A=A0exp(mit), and the mi obtained for each antioxidant were fitted to mi/m0 = alog(1/C)w. When the values of were correlated to the 13C NMR chemical shift ( ) of the ipso-carbon of the OH group and to the ionisation potential (Ip), the following expressions were obtained: = -70 + 700/Ip or = exp(-12 + 120/Ip) and = -80 + 13000/ or = exp(-13 + 23000/ ). Highly significant statistical evidence was obtained in all cases. This methodology is proposed for studies of quantitative structure-property relationships in antioxidants. is proposed as a measure of the antioxidant property of a compound.